Women entrepreneurship: a study on characteristics, challenges and management profiles of micro and small entrepreneurs in the Municipality of Monte Belo-MG (Research, Society and Development, 2021)
In view of the need to deepen knowledge about female entrepreneurship, given its current rise, especially in Brazil, the objective of the study was to analyze the profile, characteristics, and impact factors in the context of female entrepreneurs in the municipality of Monte Belo, evaluating whether the studied profile differs from the national female entrepreneur profile. The work adopted the type of descriptive research, with a qualitative approach and was carried out through semi-structured interviews, applied to ten individual entrepreneurs from different sectors in the municipality of Monte Belo. The results show that the women are mostly mature, married, have children and a high level of education. Their businesses, mostly in the service sector, are smaller and have fewer employees, and few partners. It was observed that entrepreneurship by opportunity was the main motivator to create a business. In general, the lack of financial resources and planning, as well as difficulties in managing the company were impacting factors, and the biggest challenge pointed out was the multiple working hours. Women stand out for their high level of commitment, self-confidence, and ease of communication, in addition to sensitivity, empathy, and understanding, the characteristics that make up the female management at Monte Belo. The results showed a significant relation with the profile of female entrepreneurs on a national level. It is noteworthy that the aspects developed in this work sought to contribute to the studies regarding this area in the country. Future studies in other locations in Brazil are suggested, so that it is possible to build a more comprehensive picture of the national female entrepreneurial universe.